2020
DOI: 10.5296/rae.v12i4.18103
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and Health Outcomes in Sub-Saharan Africa

Abstract: The objective of this research is to identify the institutional dimensions that are the most relevant to the improvement of health outcomes in sub-Saharan Africa. To this end, institutional quality measures are integrated into a health production model. This model is estimated by the Two-stage least squares method on a panel of 45 countries observed over the period 1996-2018. The data used are from the World Bank. The results show that the most relevant institutional dimensions that improve health outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…It increases life expectancy from 0.1745 to 0.599 years while improving the effect of school enrollment rates on lowering infant mortality rates from 0.0318 to 0.0484%. These outcomes partially support the findings of Opeloyeru et al 188 , Tadadjeu et al 189 , Iddrisu et al 190 , Alimi and Ajide 191 , Dhrifi 53 , and Asgher et al 192 , who also found the direct and spillover effects of institutional quality on health outcome indicators across different economic contexts. Interestingly, AIQ has been found to be effective in reducing the negative impact of inflationary shocks and economic volatility shocks on both life expectancy and infant mortality rates in the panel under review.…”
Section: Resultssupporting
confidence: 82%
“…It increases life expectancy from 0.1745 to 0.599 years while improving the effect of school enrollment rates on lowering infant mortality rates from 0.0318 to 0.0484%. These outcomes partially support the findings of Opeloyeru et al 188 , Tadadjeu et al 189 , Iddrisu et al 190 , Alimi and Ajide 191 , Dhrifi 53 , and Asgher et al 192 , who also found the direct and spillover effects of institutional quality on health outcome indicators across different economic contexts. Interestingly, AIQ has been found to be effective in reducing the negative impact of inflationary shocks and economic volatility shocks on both life expectancy and infant mortality rates in the panel under review.…”
Section: Resultssupporting
confidence: 82%
“…Regarding health outcomes, Rehmat et al (2020) demonstrated that institutional quality helps improve life expectancy and lower infant mortality rates. Similarly, using different proxies for institutional quality, Ouedraogo et al (2020) found that institutions contribute to increased life expectancy at birth in sub-Saharan Africa. Dhrifi (2020) found that the quality of institutions has a crucial influence on how health spending affects infant mortality rates, acting as a key factor in shaping their relationship.…”
Section: Empirical Literature On Institutions and Development Outcomesmentioning
confidence: 99%
“…Although Ouedraogo, Dianda, and Adeyele (2020) [ 45 ] support that institutional quality is paramount in healthcare efficiency, most studies [ 28 , 38 , 46 ] focus on the direct impact of health expenditure on U5MRs. Nevertheless, studies that considered institutional quality as the mediating effect in the said relationship only focused on public health expenditure.…”
Section: Literature Review On Under-five Mortalitymentioning
confidence: 99%
“…Again, some studies [ 45 ] assessed only the effect of institutional quality on five mortality, while a few studies [ 23 , 26 ] consider institutional quality as the mediating factor in the under-five mortality-health expenditure nexus. However, the current paper considers the institutional quality’s impact on the effect of each of the four health expenditure indicators on under-five mortality in SSA.…”
Section: Literature Review On Under-five Mortalitymentioning
confidence: 99%